The Role of the KWL (Know-Want-Learned) Strategy in Fostering Reading Comprehension: A Case Study at MAN 1 Parigi, Indonesia - Wiwin Suciati; Hastini Hastini (Journal of General Education and Humanities, 2023)
This research aims to prove how (KWL) Know-Want-Learn strategy can enhance the reading comprehension of MAN 1 Parigi students in the tenth grade. This research used a quantitative approach using a single pretest and posttest research design. The researcher conducted her research in two classes, one experimental and one control. In the experimental class, there were 28 students, while there were 27 in the control class. The researcher employed pretest and posttest to gather data. Paired sample t-test aided SPSS application version 25 for Windows was used to analyze the data. Based on the findings of this research, it is possible to conclude that (KWL) Know-Want-Learn strategy succeeded in improving the reading comprehension of tenth-grade students at MAN 1 Parigi. This is proven from the paired sample t-test analysis that the significance value (2-tailed) was 0.000 < 0.05, meaning there is a significant distinction within the student learning outcomes for the pretest and post-test.